Servant or Service? The Problem and a Conceptual Solution - Guy Hornsby; Ben Gleason; Dan Wathen; Brad Deweese; Meg Stone; Kyle Pierce; John Wagle; David J. Szymanski; Michael H. Stone (University of Kansas Libraries, 2017)
The present article addresses issues within U.S. collegiate sport as it pertains to the physical preparation and health and well-being of intercollegiate athletes. Specifically, the sport coach is often perceived as "all knowing" about every facet of their sport when, in fact, they typically are not formally educated or well-trained in current methods of enhancing sport performance. Often strength and conditioning coaches, who may also be poorly trained, are tied directly (financially and administratively) to the sport coach-a situation which has led to a subservient role heavily influenced by the wishes of the sport coach. This has unfortunately resulted in the multidimensional well-being of the athlete clearly not being a primary objective in many programs.